2013
DOI: 10.2320/matertrans.m2013107
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Rapidly Solidified Cu–0.81Cr–0.12Zr Alloy

Abstract: Cu0.81 mass%Cr0.12 mass%Zr alloy was spun into ribbon and then aged at different temperatures for different time. The microstructure, microhardness and electrical conductivity were investigated. It is found that the mother alloy ingot solidified under conventional conditions consists of three phases: Cu matrix, Cr and Cu 5 Zr. Rapid quenching makes Cr and Zr fully dissolve into the copper matrix. As the aging proceeds, Cr and Cu 5 Zr phases precipitate again from the matrix. The ribbon aged at 773 K for 15 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…It is worth stating that, upon solidification of the Cu–Cr–Zr system, Cu-rich precipitates are first solidified from the melt. Then, Zr-rich precipitates envelope the Cr-rich precipitates forming a Zr-rich shell around a core of Cr-rich precipitates [1,3,15,17,18,22]. Thence, the presence of Zr prevents the growth of Cr-rich precipitates upon solidification and aging while it has an insignificant effect on the grain size of the matrix structure in the studied conditions.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is worth stating that, upon solidification of the Cu–Cr–Zr system, Cu-rich precipitates are first solidified from the melt. Then, Zr-rich precipitates envelope the Cr-rich precipitates forming a Zr-rich shell around a core of Cr-rich precipitates [1,3,15,17,18,22]. Thence, the presence of Zr prevents the growth of Cr-rich precipitates upon solidification and aging while it has an insignificant effect on the grain size of the matrix structure in the studied conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The precipitate characteristics, electrical conductivities, and mechanical properties of various functional Cu-Cr-Zr alloy compositions, with and without rare earth element additions, were studied after aging at temperatures ranging from 250 to 600°C for periods ranging from 0 to 24 h [1,2,6,8,9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. All studies concluded that achieving the best integration of high electrical conductivity, high strength, high hardness, and high wear resistance can be achieved via tailoring the processing parameters and chemical composition.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations